2022-RA-1158-ESGO Uterine sarcoma. (20th October 2022) - Taghzouti, Hanae; Saoud, Mohammed Karam
Abstract : Introduction/Background: Uterine sarcomas are rare tumors, representing 3 to 5% of malignant tumors of the uterus. They are characterized by a significant histopathological and clinical diversity. Their diagnosis is not very often made until the histopathological analysis of the hysterectomy or myomectomy specimen, distinguishing between: carcinosarcoma; leiomyosarcoma; rhabdomyosarcoma; adenosarcoma; stromal sarcoma; undifferentiated sarcoma. Doppler ultrasound does not differentiate uterine sarcomas from fibroids. MRI, and in particular dynamic sequences after injection of gadolinium, can help in the diagnosis. Surgery is the first step in the management of uterine sarcoma, consisting of a total hysterectomy with bilateral adnexectomy. A pelvic curage with omentectomy will be added in case of carcinosarcoma. Methodology ten cases of uterine sarcoma treated in the department of gynecology-obstetrics I at the CHU Hassan II in Fez between 2016 and 2021 were analyzed retrospectively. Results: Of the 10 patients, 60% are multiparous, 80% postmenopausal and 01 patient has a history of uterine fibroid. 80% of our patients consulted for metrorrhagia. 90% of our patients had surgical treatment. Anatomopathological analysis of the surgical specimens revealed 07 leiomyosarcoma, 02 endometrial stromal sarcoma, and 01 adenosarcoma. Three patients received adjuvant radiotherapy, while a combined chemotherapy/radiotherapy postoperatively was indicated for one patient. Conclusion: Sarcomas are rare cancers of the uterus and their prognosis is poor. Their diagnosis must be made early, as the tumor stage is the major prognostic factor.